How Trichoderma Enhances Plant Defense Enzymes in Food Crops: Current Insights and Future Perspectives in Asia - Hasan Albana; Nurbailis Nurbailis; Darnetty Darnetty (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2024)
Food crops are plants grown for consumption by humans and animals. These crops face threats from both abiotic and biotic factors. Therefore, environmentally friendly alternative controls, such as enhancing plant resistance using Trichoderma spp, are needed. This systematic literature review provides information on the effects of Trichoderma spp. application on plant physiology, particularly focusing on defense enzymes in food crops in the Asian region. Articles on the effects of Trichoderma application on food crop defense enzymes in Asia were retrieved from PubMed and Scopus. The literature search yielded 3,022 articles from these databases. Four criteria were established for study inclusion: i) studies involving Trichoderma spp.; ii) studies using food crops as the subject; iii) studies conducted in Asia; and iv) studies evaluating at least one defense enzyme activity. In this systemic review, we found at least 100 isolates of Trichoderma spp. that can increase plant resistance, as indicated by the increase of plant defense enzymes in Asia. The studies were mostly reported in India and China. Rice is the most frequently studied crop. The most frequently used is T. harzianum. Meanwhile, the defense enzymes tested are peroxidase, polyphenol oxidase, phenylalanine ammonia-lyase, chitinase, and β-1,3-glucanase. The most commonly used inoculation method is seed treatment in a controlled environment such as a greenhouse. More research on changes in plant enzymes due to Trichoderma spp. application is recommended to assess its effectiveness in practical, real-world settings, especially in field conditions.